The Procedure for Determining Regional Tax Increases in Indonesia: An Analysis of the Normative and Implementational Legal Gaps - Aminah, Siti; Mohammad Sirojuddin (VRISPRAAK : International Journal of Law, 2025)
Regional autonomy positions regional taxation as a primary pillar of local revenue (Pendapatan Asli Daerah or PAD). The procedural framework for determining tax rate increases, as regulated in Law No. 28 of 2009 on Regional Taxes and Retributions (PDRD) and Law No. 1 of 2022 on Financial Relations between the Central and Regional Governments (HKPD), is designed to ensure legal certainty and fairness. However, in practice, these normative procedures often confront diverse social, political, and institutional realities at the regional level. This research aims to analyze the gap between the normative procedures for determining regional tax increases and their implementation across various regions in Indonesia, while also evaluating the integration of good governance principles within the process. Using a normative juridical method combined with a qualitative approach, the study examines secondary data drawn from the aforementioned laws and local regulations (Perda) in selected provinces such as Jakarta, Bali, East Kalimantan, and East Nusa Tenggara. The data are further supported by recent academic publications within the last five years. The findings reveal significant variations in implementation despite the comprehensive legal framework. Such gaps stem from differing institutional capacities, local political dynamics, and economic lobbying. The study concludes that the legitimacy and effectiveness of regional tax procedures depend not solely on legal compliance but also on the capacity of local actors to contextualize legal norms. Strengthening regional institutional capacity and promoting meaningful public participation are therefore crucial to bridging the gap between law and practice.